2013
DOI: 10.3382/ps.2012-02528
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis PB6 improves intestinal health of broiler chickens challenged with Clostridium perfringens-induced necrotic enteritis

Abstract: Necrotic enteritis (NE) is an enterotoxemic disease caused by Clostridium perfringens that results in significant economic losses, averaging damage of $0.05 per bird. The present study investigated the influence of a dietary supplement, Bacillus subtilis PB6, on performance, intestinal health, and gut integrity against C. perfringens-induced NE in broiler birds. Bacillus subtilis PB6 (ATCC-PTA 6737) is a natural strain isolated from healthy chicken gut that has been shown in in vitro to produce antimicrobial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
107
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 16 publications
16
107
0
1
Order By: Relevance
“…In addition, the broad tips of the intestinal villi with the proliferation of enterocytes, together with heterophil infiltration and oedema in the lamina propria, were consistent with the results by Olkowski et al (2006). The results of this study are consistent with those of Jayaraman et al (2013), who reported that birds infected with C. perfringens showed markedly thickened mucosa, haemorrhages and intestinal ballooning. Asaoka et al (2004), Yang et al (2009) and Khambualai et al (2010) found that NE was characterized by extensive necrosis in the mucosa and haemorrhages, as well as inflammatory cell infiltration in birds infected with C. perfringens.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, the broad tips of the intestinal villi with the proliferation of enterocytes, together with heterophil infiltration and oedema in the lamina propria, were consistent with the results by Olkowski et al (2006). The results of this study are consistent with those of Jayaraman et al (2013), who reported that birds infected with C. perfringens showed markedly thickened mucosa, haemorrhages and intestinal ballooning. Asaoka et al (2004), Yang et al (2009) and Khambualai et al (2010) found that NE was characterized by extensive necrosis in the mucosa and haemorrhages, as well as inflammatory cell infiltration in birds infected with C. perfringens.…”
Section: Resultssupporting
confidence: 82%
“…Abdel-Raheem et al (2012) and Sen et al (2012) reported that dietary supplementations of B. subtilis increased villus length in comparison with the dietary control. In a later study, B. subtilis was found to increase the length and surface area of villi when compared with the positive control group under challenge by C. perfringens (Jayaraman et al, 2013). Higher surface area in villi was reported as a result of MOS supplementation as prebiotic compared with the control group (Loddi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of higher mean Clostridium perfringens count in the birds exposed for necrotic enteritis challenge devoid of supplementation of B. subtilis (T3) as compared to any of the other treatment groups or healthy control birds and decrease in mean concentration of Clostridium perfringens count in healthy supplemented with B. subtilis group is comparable with results of Jayaraman et al (2013) where they reported significantly lower count of Clostridium perfringens; Maruta et al (1996) also observed protection of birds against Clostridium perfringens using B. subtilis C-3102 in the feed . The intestinal microbial analysis for Clostridium perfringens count concluded that supplementation of Bacillus subtilis reduces the damage caused in necrotic enteritis infection in broiler birds as well as under disease free condition supplementation of B. subtilis helps in improving gut health and overall growth performance of birds.…”
Section: Colony Forming Unit (Cfu) Countsupporting
confidence: 76%
“…presence of higher villi length in necrotic enteritis challenged birds supplemented with B. subtiis and in non-infected group supplemented with B. subtils are in consistency with Samanaya and Yamuchi (2002) as they have also reported improved histologies in probiotic supplemented birds in terms of villus length. It was also reported by Jayaraman et al (2013) that B. subtilis supplemented birds showed better villi health in comparison to any other groups which indicated that it could be possible that Bacillus subtilis acts independent of the infection in improving the gut health.…”
Section: Colony Forming Unit (Cfu) Countmentioning
confidence: 87%